2013
DOI: 10.1002/anie.201308820
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light Sensitization of Vinyl Azides by Transition‐Metal Photocatalysis

Abstract: Irradiation of vinyl and aryl azides with visible light in the presence of Ru photocatalysts results in the formation of reactive nitrenes, which can undergo a variety of C–N bond-forming reactions. The ability to use low-energy visible light instead of UV in the photochemical activation of azides avoids competitive photodecomposition processes that have long been a significant limitation on the synthetic utility of these reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
113
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(114 citation statements)
references
References 42 publications
0
113
0
1
Order By: Relevance
“…Our laboratory previously studied the use of visible light absorbing transition metal complexes to sensitize vinyl azides towards intramolecular heterocyclic ring-closing reactions (Scheme 1). 11 Quite recently, König and coworkers reported an intriguing method for photocatalytic amidation of electron-rich heterocycles, the key step of which was proposed to involve triplet sensitization of a benzoyl azide. 12 To the best of our knowledge, however, the use of triplet sensitizers to promote chemoselective intermolecular alkene aziridination reactions has not previously been described.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory previously studied the use of visible light absorbing transition metal complexes to sensitize vinyl azides towards intramolecular heterocyclic ring-closing reactions (Scheme 1). 11 Quite recently, König and coworkers reported an intriguing method for photocatalytic amidation of electron-rich heterocycles, the key step of which was proposed to involve triplet sensitization of a benzoyl azide. 12 To the best of our knowledge, however, the use of triplet sensitizers to promote chemoselective intermolecular alkene aziridination reactions has not previously been described.…”
mentioning
confidence: 99%
“…14 Finally, we computationally estimated the lowest-energy triplet excited state of ethyl azidoformate to be ~54 kcal/mol, 15 thermodynamically within a range accessible by the Ir complexes we have previously exploited as energy transfer photocatalysts. 11,16 …”
mentioning
confidence: 99%
“…In addition, PRC for azidyl radical addition [7] has yet to be investigated, and would represent av ersatile and mild approach to valuable organic azides.P RC applications of azides to date have involved nitrene generation from vinyl or aryl azides. [8] A single report from Masson, Magnier,a nd co-workers [9] describes the trifluoromethyl azidation of double bonds using an azide anion introduced from TMSN 3 .…”
mentioning
confidence: 99%
“…18 Important recent studies from Yoon and co-workers demonstrated that photolytic conversion of dienyl azides 39 into reactive nitrenes 40 , with visible light in the presence of a Ru photocatalyst was an attractive approach to the construction of pyrroles 41 (Scheme 7). 19 The use of low-energy visible light precludes competitive photodecomposition processes typically associated with UV irradiation, and makes this approach more attractive and useful.…”
Section: Thermal- or Photo-induced Reactions Of Vinyl Azidesmentioning
confidence: 99%